Perspectivas de empoderamento e de resistência em um modelo de economia compartilhada na ótica da teoria das transições : caso Uber no contexto brasileiro - Dal Bó, Gicelda Julia (2017)
This dissertation explores structures of power from the point of view of empowerment and resistance in a shared economy model, having Uber (since its arrival in the country) as object of study. To this end, it relies on a qualitative method of interpretativist approach through a single case study. By identifying the agents' discourses of the urban mobility socio-technical system, in the voice of media vehicles and specialized websites, this research proposes to analyze how power structures are organized. The study lists three perspectives, an “economic model”, a “business model” and “sustainable development”, built to group the “two sides of the same coin”, empowerment and resistance, proposing a “conversation” between them. It presents a view of the relationship with the collectivity through two mechanisms, also of opposing forces: “quest for legitimacy” and “reinforcement to the status quo”. In a complementary way, it proposes a discussion section about uberism and its variations. Among the aspects listed in this section, issues of regulation and characteristics of the so-called Uber economy stand out. It brings, as theoretical basis, concepts of the Transition Theory for Sustainable Development, the Multiple Level Perspective (MLP) and an applied study that links sharing economy to the notion of socio-technical systems. With this, it seeks to demonstrate the “game” of forces between empowerment and resistance in the Brazilian context of the socio-technical system of urban mobility. A combination of technological trajectories that have been destabilizing and pressuring the existing socio-technical structures pointed out for the existence of transitions to sustainable development.